Constancy of pressure-rate product in pacing-induced angina pectoris. - Cokkinos, D V (1976)
The pressure-rate product during anginal pain produced by right atrial pacing was studied in 12 patients before, during, and after an angiotensin infusion sufficient to produce a significant rise in blood pressure. During the infusion the pain occurred at a significantly lower heart rate (P less than 0.001). However, the pressure-rate product was similar during anginal pain before and during the angiotensin-induced hypertension and after it wore off. Our studies support the concept that in each individual there is a constant level of myocardial oxygen consumption, as expressed by the pressure-rate product, at which anginal pain occurs.